Propaganda Khilafah HTI di Indonesia - Ahmad Khotim Muzakka (JURNAL PENELITIAN, 2017)
This article presents contemporary issues related to the khilafah discourse in the online media http://hizbut-tahrir.or.id. The site is the official page of Hizbut Tahrir Indonesia (HTI). The researchers focus on contemporary issues discussed on the related pages in order to find out the theme of their discussion. The purpose of this study is to describe the construction of khilafah discourse, especially in contemporary issues. Another goal is to identify the character of the khilafah discourse used. The results of this study indicate that there are three main issues discussed on hizbut-tahrir.or.id. First, the dangers of neoliberalism and neoimperialism. Second, terrorism and violence. Third, environmental issues. The character of the khilafah discourse is as follows. First, it uses history as a form of religious legitimacy. Second, it prominently displays Islamic identity.